The right ventricle in tetralogy of Fallot: adaptation to sequential loading - Alipour Symakani, Rahi S.; van Genuchten, Wouter J.; Zandbergen, Lotte M.; Henry, Surya; Taverne, Yannick J. H. J.; Merkus, Daphne; Helbing, Willem A.; Bartelds, Beatrijs (Frontiers in Pediatrics, 2023)
Right ventricular dysfunction is a major determinant of outcome in patients with complex congenital heart disease, as in Tetralogy of Fallot. In these patients, right ventricular dysfunction emerges after initial pressure overload and hypoxemia, which is followed by chronic volume overload due to pulmonary regurgitation after corrective surgery. Myocardial adaptation and the transition to right ventricular failure remain poorly understood. Combining insights from clinical and experimental physiology and myocardial (tissue) data has identified a disease phenotype with important distinctions from other types of heart failure. This phenotype of the right ventricle in Tetralogy of Fallot can be described as a syndrome of dysfunctional characteristics affecting both contraction and filling. These characteristics are the end result of several adaptation pathways of the cardiomyocytes, myocardial vasculature and extracellular matrix. As long as the long-term outcome of surgical correction of Tetralogy of Fallot remains suboptimal, other treatment strategies need to be explored. Novel insights in failure of adaptation and the role of cardiomyocyte proliferation might provide targets for treatment of the (dysfunctional) right ventricle under stress.